Sistema de tarifação pré-paga de energia elétrica: avaliação da experiência internacional e da aplicação no Brasil - PANTOJA, Agnaldo Martins (2018)
This paper presents an analysis of the electricity prepaid charging system in pilot projects in Brazil and applications in other countries, focusing on their main advantages and disadvantages both for the consumer and for the dealership of electricity. It also makes a comparison of the conventional system (postpaid) and the pre-paid system. Talks about the rules of the sport in Brazil, its reviews together with consumer protection agencies, their limitations and obstacles.